Dividend Policy as Moderating Variable to the Consumer Goods Company on the Indonesia Stock Exchange - Nagian Toni; Enda Noviyanti Simorangkir; Thomas Sumarsan Goh (Bina Nusantara University, 2021)
The capital market in Indonesia includes many companies from several sectors. One company that cannot be separated from the Indonesian stock market is a consumer goods company. The research aimed to analyze the effect of profitability and capital structure on the company with dividend policy as moderating variable to the consumer goods companies registered on the Indonesia Stock Exchange in the period of 2014-2018. The population in the research was consumer goods companies with subsector of food and drink, cigarette, cosmetic pharmacy, and household goods and appliances. The research applied purposive sampling and obtained 15 companies with 5 years of observation or around 75 samples. Then, the data were analyzed using Smart PLS 3.0. The analysis result shows that profitability, capital structure, and company size positively and significantly influence the company value. However, dividend policy cannot moderate the effect of profitability and capital structure on the company value. The dividend policy can moderate the effect of company size on the company value. Then, profitability, capital structure, and company size influence the company value of 88,6%, while the other factors influence the rest. Investors should decide on issuers with high profitability above 5%, the optimal capital structure with the debt-to-equity ratio between 0,8-1,2, and total assets above five trillion Rupiah.